Determination of minimum inhibitory concentration of Chromium Salts on the microbial strains isolated from Buriganga River-bed soil - Zaman, Farzana Ishrat (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.